2016
DOI: 10.1111/jai.13197
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight and length-length relationships for 23 fish species of Porto Primavera reservoir, Upper Paraná River, Brazil

Abstract: Summary The study presents length–weight relationships (LWR) and length–length relationships (LLR) for 23 fish species captured in the Porto Primavera Reservoir, Upper Paraná River. Seventeen of the LWRs and 20 of the LLRs are reported for the first time. New maximum standard lengths are presented for 17 species as well as weights for three species and new total weight records for 19 species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
6
1
1
Order By: Relevance
“…The maximum lengths (SL) reached in this study were higher than those observed in the Porto Primavera reservoir by Marques et al (2016) for C. piquiti (SL = 49.5 cm) and C. nagelli (SL = 19.5 cm). Samples of P. mesopotamicus, C. haroldoi and H. ancistroides captured in Três Irmãos reservoir presented higher maximum sizes than those obtained in Gubiani et al (2009) for 30 neotropical reservoirs.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The maximum lengths (SL) reached in this study were higher than those observed in the Porto Primavera reservoir by Marques et al (2016) for C. piquiti (SL = 49.5 cm) and C. nagelli (SL = 19.5 cm). Samples of P. mesopotamicus, C. haroldoi and H. ancistroides captured in Três Irmãos reservoir presented higher maximum sizes than those obtained in Gubiani et al (2009) for 30 neotropical reservoirs.…”
Section: Discussioncontrasting
confidence: 71%
“…For reservoirs, mainly in Brazil, is clear the needs of new studies in this scope. For instance, for the upper Paraná river, which hold a series of reservoirs (see Agostinho et al, 2008), just a few works were published (e.g., Benedito-Cecílio et al, 1997;Angelini and Agostinho, 2005;Gubiani et al, 2009;Oliva-Paterna et al, 2009;Marques et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…LWRs were determined using the linear regression: log TW − log a + b log TL, where TW is the total weight (in grams), TL is the total length (in cm), “ a ” is the intercept and “ b ” is the slope of the linear regression (Froese, ; Nobile et al., ). For TL – SL relationships (LLRs), the determination was made using the linear regression SL = a + b TL (Marques, Nobile, Dias, & Ramos, ). Outliers were removed in both analyses using a log TW − log SL or log TL − log SL plot (Nobile et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…A series of morphometric measurements were made with a ruler to the nearest mm following the methods of Jégu and Dos Santos (2001) (Table 1). The total length of the specimens ranged from 95.0 to 296.2 mm, which is larger than the lectotype NMW 17995 (162 mm), the paralectotype NMW 16230 (154 mm) (Jégu and Dos Santos 2001), the three specimens examined by Jégu (2003) (122, 154, and 162 mm), or the maximum total length given by Marques et al (2016). Therefore, a new maximum total length has been recorded for this species in the present study.…”
Section: Resultsmentioning
confidence: 77%